Anatomical sacral slope, a new pelvic parameter, is associated with lumbar lordosis and pelvic incidence in healthy Japanese women: A retrospective cross-sectional study. (11th December 2019) - Suzuki, Hayato; Imai, Norio; Nozaki, Asami; Hirano, Yuki; Endo, Naoto
Purpose: Anatomical sacral slope (a-SS), a pelvic anatomical parameter that does not require the center of the femoral head, strongly correlates with pelvic incidence (PI) during three-dimensional measurements in normal subjects. Sagittal alignment of spinal and pelvic parameters is typically evaluated using two-dimensional radiographs; however, the relationship between a-SS and PI has not been evaluated using radiographs. This study aimed to evaluate the correlation between a-SS and other spinal and pelvic parameters using radiographs. Methods: We evaluated 144 healthy women. Using sagittal radiographs, we measured lumbar lordosis (LL), thoracic kyphosis, PI, SS, pelvic tilt, and a-SS, which were defined as the angle between the superior end plate of S1 and a line perpendicular to the anterior pelvic plane. Pearson coefficients were used to determine correlations, and intraobserver and interobserver intraclass correlation coefficients (ICCs) were used for validation. Results: There was a strong correlation between PI and a-SS ( r = 0.756). Moreover, correlations between a-SS and LL and between PI and LL were similar ( r = 0.661 and r = 0.554, respectively). The intraobserver ICCs were 0.884 for a-SS and 0.840 for PI. The interobserver ICCs were 0.856 for a-SS and 0.653 for PI. Conclusion: a-SS was strongly correlated with PI. The correlation between a-SS and LL was equivalent to the correlation between PI and LL. Moreover, the ICC for a-SS was larger than that of PI. This study suggests that a-SS is a useful new pelvic anatomical parameter that can be used instead of PI.